Burnout and coping strategies among future healthcare professionals: a structural equation modelling approach - Ivančević, Sonja V.; Maričić, Milica M.; Ivanović, Tatjana R.; Tepšić Ostojić, Vesna J.; Stošić, Sanja S. (Vojnosanitetski pregled, 2022)
Background/Aim. To reduce the risk of burnout development in medical professionals, it is important to identify the contributing factors as early as in their schooling years. The aim of this study was to propose a model for determining the relationship between the coping strategies used by medical high school and medical faculty students and burnout. Methods. The cross-sectional study included 164 students of Medical High School (80.5% female and 19.5% male) and 344 students of the Faculty of Medicine University of Belgrade, Serbia (76.9% female and 23.1% male). The model exploring the relationship between coping strategies (measured by the Brief COPE scale) and burnout [measured by the Copenhagen Burnout Inventory-student version (CBI-S) scale] was tested using structural equation modelling (SEM) analysis. Results. When copied with stress, Medical High School students used Acceptance, Venting, Behavioural Disengagement, and Planning, which increased their burnout, but they did not use any strategies to help them reduce burnout. When copied with stress, Faculty of Medicine students used Planning, Acceptance, Humour, Venting, Behavioural Disengagement, Self-Blame, and Substance Use, which increased their burnout, and Positive Reframing, which helped them reduce burnout. Conclusion. The results of this research showed an evident lack of using adaptive coping strategies with both groups of respondents. Proper education could help them replace these dysfunctional coping strategies with constructive ones.